Argumentation of Gender Equality in the Interpretation of Jilbab Verse by Amina Wadud's Perspective - Zulfikar, Eko; Mustaqim, Abdul (QOF, 2024)
This article discusses Amina Wadud’s gender equality argument in interpreting the verse of jilbab in QS. al-Aḥzab [33]: 59. This is based on the historical fact that the verse is always associated with the command for women to veil and distinguish between free and enslaved person women during the jahiliyah period. Using a descriptive-analytical qualitative method with Amina Wadud’s gender analysis approach, this article concludes that the understanding of QS. al-Aḥzab [33]: 59 warns Muslims always to control themselves, guard and protect women, and not neglect the commandments of Allah. From the perspective of Amina Wadud’s progressive interpretation, QS. al-Aḥzab [33]: 59, which is initially interpreted as women getting orders to veil and not dress openly as self-protection from sexual harassment from the opposite sex, develops to get protection from all kinds of dangers that befall it. This verse instructs the prohibition of harming or harassing women because, in the public sphere, they have a strategic position to foster aspects of community morality. Changes supported by modern currents show that the opportunity for women’s contribution has developed relatively high, so the umbrella of protection for women has become a significant thing. This is in line with Pasal 28G Ayat (1) UUD 1945, which mandates that the state guarantee the enjoyment of rights without discrimination and gender differences. Thus, Amina Wadud’s argument indicates that protection under any conditions for women must be established to have a positive impact on the progress of sexually-based morals in society and eliminate the culture of objectification attached to women.